2010
DOI: 10.5304/jafscd.2010.011.013
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits, Challenges, and Strategies of Adults Following a Local Food Diet

Abstract: Supported in part by a variety of popular books, websites, and other media, the interest in local food is building dramatically, and a growing number of people are increasing their purchases of local food. This paper describes a study that explored the perceived benefits and challenges of following a diet consisting exclusively of local food in southwestern Virginia, as well as the strategies for coping with its limitations. Nineteen individuals participated in a four-week Local Food Diet Challenge, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…In line with previous studies of local food consumption, the findings of this study reveal that Australian consumers are concerned with egoistic motivations related to their health and personal well-being (Byker et al, 2010;Weatherell et al, 2003) as well as issues of food safety (Peters et al, 2008). Egoistic motivations were found to be positively associated with favourable beliefs toward purchasing local foods, interest in traceability of food, and with propensity to buy local food.…”
Section: Theoretical Implicationssupporting
confidence: 87%
“…In line with previous studies of local food consumption, the findings of this study reveal that Australian consumers are concerned with egoistic motivations related to their health and personal well-being (Byker et al, 2010;Weatherell et al, 2003) as well as issues of food safety (Peters et al, 2008). Egoistic motivations were found to be positively associated with favourable beliefs toward purchasing local foods, interest in traceability of food, and with propensity to buy local food.…”
Section: Theoretical Implicationssupporting
confidence: 87%
“…Numerous books, magazines, TV programs, and newspaper articles seem to give this trend a direction in particular. As a matter of fact, from the recent times to today, dozens of books on local dietary lists and human histories that have spent years on these diets continue to be on the shelves (Byker, Rose, & Serrano, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In two studies, consumers were found to be willing to pay a price premium for locally-produced food (Carpio & Isengildina-Mass, 2008;Ruth & Rumble, 2015). Local food has been reported to be perceived as having higher quality based on search and experience attributes such as freshness and taste (Byker, Rose, & Serrano, 2010;Chambers, Lobb, Butler, Harvey & Traill, 2007;Dentoni et al, 2009;Goodwin, 2013;Zepeda & Leviten-Reid, 2004). Researchers have reported that consumers believed local food has credence qualities of supporting local producers, supporting the local economy, as well as being environmentally friendly (Darby, Batte, Ernst, & Roe, 2008;Nimon & Beghin 1999;Loureiro, McCluskey, & Mittelhammer, 2002;Thilmany, Bond, & Bond, 2008).…”
Section: Conceptual Model and Literature Reviewmentioning
confidence: 99%